2013
DOI: 10.1038/ki.2012.373
|View full text |Cite
|
Sign up to set email alerts
|

Low mannose-binding lectin serum levels are associated with reduced kidney graft survival

Abstract: Activation of the complement system is initiated by the alternative, the classical, or the lectin pathway. As the complement system is involved in the pathophysiology of graft rejection after kidney transplantation, we investigated the possible role of mannose-binding lectin in kidney transplantation and the influence of human leukocyte antigen (HLA) immunization on this process. In a prospective study of 544 kidney transplant patients over a follow-up period of 5 years, low serum levels of this lectin at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…Previous reports either did not find a significant association between MBL status and acute rejection 36 or concentrated on long-term graft and patient outcomes. 16,17,26 The finding of robust and clear-cut association between low MBL status and increased incidence of ACR seen in our study is likely due to size and homogeneity of the prospectively followed cohort being treated with recent-era immunosuppressive protocols. Moreover, the relatively homogeneous drug prescription, in ), B (G54D, rs1800450), and C (G57E, rs1800451), respectively, and the wild-type allele of each is referred to as genotype A. MBL genotype Y refers to presence of rare variant C of promoter SNP G221C (rs7096206) and genotype X as wild-type allele G of that polymorphism.…”
Section: Golshayan Et Al: Lectin Pathway and Rejection After Transmentioning
confidence: 69%
See 2 more Smart Citations
“…Previous reports either did not find a significant association between MBL status and acute rejection 36 or concentrated on long-term graft and patient outcomes. 16,17,26 The finding of robust and clear-cut association between low MBL status and increased incidence of ACR seen in our study is likely due to size and homogeneity of the prospectively followed cohort being treated with recent-era immunosuppressive protocols. Moreover, the relatively homogeneous drug prescription, in ), B (G54D, rs1800450), and C (G57E, rs1800451), respectively, and the wild-type allele of each is referred to as genotype A. MBL genotype Y refers to presence of rare variant C of promoter SNP G221C (rs7096206) and genotype X as wild-type allele G of that polymorphism.…”
Section: Golshayan Et Al: Lectin Pathway and Rejection After Transmentioning
confidence: 69%
“…Recently, Bay et al have used a lower median cutoff value (#454 ng/ml) and have shown that low serum MBL levels were associated with decreased 5-year death-censored graft survival. 26 Interestingly, the strongest association was seen in non-immunized patients receiving a kidney from a deceased donor. 26 When stratifying our data, we also observed a strongest association between low MBL status and ACR in recipients of deceased as compared to living donors (Supplementary Figures S4 and S5).…”
Section: L I N I C a L I N V E S T I G A T I O Nmentioning
confidence: 99%
See 1 more Smart Citation
“…A different study associated low MBL levels with poor renal allograft function and survival in non-HLA sensitised patients [56]. These differences may arise from the detection assay used with different antibodies binding high or low-order oligomers of MBL.…”
Section: Complement Activation Pathways In Ir Injurymentioning
confidence: 99%
“…Its carbohydrate recognition domains bind in a calciumdependent manner to patterns of carbohydrate residues found on microorganisms. MBL exerts an important role in the innate immune system, and several studies have indicated that low levels of MBL affect the outcome of infectious diseases, critical illness, and kidney graft survival (8)(9)(10). Interestingly, high levels of MBL offer protection against invading microorganisms but may confer biological disadvantages in other situations (11).…”
mentioning
confidence: 99%